Predicting acute renal failure in Bothrops snakebite patients in a tertiary reference center, Western Brazilian Amazon - Alves, Eliane Campos (PLoS One, 2018)
Acute Kidney Injury (AKI) is the main systemic complication and cause of death in viperid envenomation. Although there are hypotheses for the development of AKI, the mechanisms involved are still not established. The aim of this study was to evaluate the clinical-laboratorial-epidemiological factors associated with AKI in victims of Bothrops sp envenomation. This is an observational study carried out at the Fundação de Medicina Tropical Dr. Heitor Vieira Dourado. AKI was defined according to the guidelines of the Acute Kidney Injury Network (AKIN). Among the 186 patients evaluated, AKI was observed in 24 (12.9%) after 48 hours of admission. Stage I was present in 17 (70.8%) patients, II in 3 (12.5%) and III in 4 (16.7%). Epidemiological characterization showed predominance of men, occurrence in rural areas, aged between 16–60 years, feet as the most affected anatomical region, and time to medical assistance less than 3 hours. Hypertension and diabetes were the comorbidities identified. Most of the accidents were classified as moderate, and clinical manifestations included severe pain, mild edema, local bleeding and headache. Laboratory results showed blood uncoagulability, hypofibrinogenemia, leukocytosis, increase of creatine kinase, and high lactate dehydrogenase levels. Multivariate analysis showed an association with high LDH levels [AOR = 1.01 (95% CI = 1.01–1.01, p<0.002)], local bleeding [AOR = 0.13 (95%CI = 0.027–0.59, p<0.009)], and the presence of comorbidities [AOR = 60.96 (95%CI = 9.69–383.30; p<0.000)]. Herein, laboratory markers such as high LDH levels along with local bleeding and comorbidities may aid in the diagnosis of AKI.